Forage diversity, conservation and use - Hanson, Jean; Schultze-Kraft, Rainer; Peters, Michael; Wenzl, Peter; Amri, Ahmed; Shehadeh, Ali; Yazbek, Mariana (CAB International, 2020)
This chapter outlines the scientific and development impacts of forage diversity conservation, characterization and distribution work under the international network of forage collections in CGIAR. The focus for the future will continue to be on the core operations that are essential to conserve and manage the diversity with increased emphasis on those that will ensure efficiency and value for money in gene bank operations. In addition to these essential activities, there are opportunities to be more forward and outward looking and to link with activities in the Livestock CRP and the Excellence in Breeding Platform, as well as to contribute to the global system of plant genetic resources, support the FAO Global Plan of Action and contribute to the Sustainable Development Goals.